Pseudophoenix sargentii: Buccaneer Palm - Mica McMillan; Kara McCoy (EDIS)
This publication is intended for anyone interested in identifying and utilizing this Florida native palm in their landscape. Pseudophoenix sargentii is native to the Caribbean, Belize, Mexico (Quintiana Roo), and Navassa Island. This palm is widely adapted to south Florida soils, is salt tolerant, and grows well in full sunlight. As an attractive palm with blue-gray fronds and an erect trunk, this palm would make a beautiful addition to any landscape, but its slow growth and lack of cold tolerance have prevented it from being widely utilized in Florida landscapes.